If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + 5 + -5x = -1 Reorder the terms: 5 + 9x + -5x = -1 Combine like terms: 9x + -5x = 4x 5 + 4x = -1 Solving 5 + 4x = -1 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + 4x = -1 + -5 Combine like terms: 5 + -5 = 0 0 + 4x = -1 + -5 4x = -1 + -5 Combine like terms: -1 + -5 = -6 4x = -6 Divide each side by '4'. x = -1.5 Simplifying x = -1.5
| 0.094=(1/2.05)*(0.14)+(1.05/2.05)*(0.65)*d | | 4a-(2a-6)=14 | | 9x+3x+7=28+3x+2x | | 13+8x=28 | | X^3-3x^2-36x+56=0 | | 7y-2=-3y | | 3x+4=0.5-2 | | 3-8x=6x-9 | | 5x^3-21x^2-21x+5=0 | | .1(8250-.1y)+.01y=825 | | .1x+.01y=825 | | .09x+.03y=963 | | 6x+4=x+59 | | x+7=-4+2x | | 8+5x=7x-10 | | x+10+6x=66 | | 51=6x+3x+6 | | 3[2x+5]=21 | | 6+x+6x=83 | | 35-8x=17 | | x+8+4x=23 | | x+8+x=18 | | 76=5x+4x+4 | | -TX+3BY=C | | -8(-3x+2)=2x | | 3x+90=-78-9x | | -101-11x=27-3x | | -6+3(-2x+12)=144 | | 34=3x-4(-2x+8) | | 34=3x-4(-2+8) | | 41+x=-9-119 | | 0.04x+0.08(24)=0.04(2x+24) |